The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.ijsu.2014.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic ultrasonography versus intra-operative cholangiogram for the detection of common bile duct stones during laparoscopic cholecystectomy: A meta-analysis of diagnostic accuracy

Abstract: LUS is a potentially useful imaging modality to confirm the absence of CBD stones without needing to cannulate the biliary system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 29 publications
3
22
0
2
Order By: Relevance
“…It was shown that LUS was a potentially useful imaging modality to confirm the absence of CBD stones without needing to cannulate the biliary system. 8 In this study, the ability of LUS to detect and exclude gall bladder and CBD stones was examined and found to have sensitivity and specificity of 94.8% and 100% respectively, which was comparable to previous reports (80%-100%), and (98%-100%). 15,16 In another study to compare between LUS and IOC, LUS was superior to cholangiography with respect to its safety, shorter examination period, and ease of administration in all patients.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It was shown that LUS was a potentially useful imaging modality to confirm the absence of CBD stones without needing to cannulate the biliary system. 8 In this study, the ability of LUS to detect and exclude gall bladder and CBD stones was examined and found to have sensitivity and specificity of 94.8% and 100% respectively, which was comparable to previous reports (80%-100%), and (98%-100%). 15,16 In another study to compare between LUS and IOC, LUS was superior to cholangiography with respect to its safety, shorter examination period, and ease of administration in all patients.…”
Section: Discussionsupporting
confidence: 85%
“…2,7 However, routine IOC during LC is often not performed because of increased operative time, radiation, and failure rate. 8 LUS is an attractive alternative with several potential advantages. The main advantages of LUS are that it does not involve ionizing radiation, is quicker to perform, has a lower failure rate and can be repeated during the procedure as required.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, laparoscopic ultrasound uses a flexible probe dressed in a sterile sheath to evaluate both ductal anatomy and the hepatic vasculature. In an attempt to try and demonstrate one method superior to the other, Aziz et al [14] performed a meta-analysis including 11 studies whose results demonstrated no significant difference in either sensitivity or specificity between each method. However, more recent studies have been able to demonstrate a higher specificity, in some cases nearly 100%, using laparoscopic ultrasound [15] .…”
Section: The Dichotomy Of Biliary Duct Imaging In Acute Cholecystitismentioning
confidence: 99%
“…[1][2][3][4][5] Routine intraoperative cholangiography (IOC) during LC remains a controversial issue and a growing number of surgeons are abandoning it. 6 Preoperative magnetic resonance cholangiopancreatography can be used to detect choledocholithiasis that can be cleared with endoscopic retrograde cholangiopancreatography (ERCP). If choledocholithiasis is detected after a cholecystectomy, ERCP is performed postoperatively.…”
Section: Introductionmentioning
confidence: 99%